DA'WAH STRATEGIES TO INCREASE THE UNDERSTANDING OF FARAIDH SCIENCE IN SOCIETY: STRATEGI DAKWAH UNTUK MENINGKATKAN PEMAHAMAN ILMU FARAIDH DI MASYARAKAT - Adnan, Mohammad; Uyuni, Badrah (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2021)
This study aims to analyze the implementation and constraints that affect the application of Islamic inheritance law among Muslims. This research is a qualitative research, using the methods of descriptive approach, sociology, normative theology and historical. Research shows that the implementation of Islamic inheritance law is more dominantly done in the family due to various factors. The special portion provided for the heirs is owned by the parents and is in absolute control. The application of the law for the division of property is always done by distributing it to the heirs by family without looking at the provisions of God's law. Problems in the application of Islamic inheritance law include the thickness of customary law and the low understanding of Islamic inheritance law (Ilmu Faraidh). Here the da'wah to teach the Science of Faraidh and various sciences of jurisprudence that began to understand the science of Faraidh became a must done by the community. And there is a need for systematic strengthening of da'wah so that knowledge is understood in a kaffah manner so that the application of maqashid syariah becomes more comprehensive.